2015
DOI: 10.1515/intag-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vermicompost and Water Treatment Residuals on Soil Physical Properties and Wheat Yield

Abstract: The application of vermicompost and water treatment residuals to improve the physical properties in the salt affected soils is a promising technology to meet the requirements of high plant growth and cost-effective reclamation. Therefore, the aim of this study was to investigate the effect of vermicompost and its mixtures with water treatment residuals on selected physical properties of saline sodic soil and on wheat yield. The treatments were vermicompost, water treatment residuals, vermicompost + water treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…Heil and Barbarick (1989) found that low (5 g kg −1 ) application rates of Al and Fe WTRs to soils increased yield of sorghum-sudangrass (Sorghum bicolor L. Moench), attributed to their Fe contributions and pHincreasing abilities. During trials of co-application of WTRs and vermicomposts, Ibrahim et al (2015) found that a 2:1 ratio of WTR to vermicompost with a combined application rate of 5 g kg −1 resulted in greater wheat yields than all other treatments tested, which included pure vermicompost and control (i.e. dried and sieved soil only) treatments.…”
Section: Land Application For General Soil Improvementmentioning
confidence: 99%
“…Heil and Barbarick (1989) found that low (5 g kg −1 ) application rates of Al and Fe WTRs to soils increased yield of sorghum-sudangrass (Sorghum bicolor L. Moench), attributed to their Fe contributions and pHincreasing abilities. During trials of co-application of WTRs and vermicomposts, Ibrahim et al (2015) found that a 2:1 ratio of WTR to vermicompost with a combined application rate of 5 g kg −1 resulted in greater wheat yields than all other treatments tested, which included pure vermicompost and control (i.e. dried and sieved soil only) treatments.…”
Section: Land Application For General Soil Improvementmentioning
confidence: 99%
“…Therefore, it can be assumed that various organic compounds are released with the disintegration of sugarcane pith during the incubation period, which also facilitates aggregate formation. The sugarcane pith also possibly results in an increase in the release of soil agglutinants such as polysaccharides as a result of their decomposition because of an increase in biological activity (Sanjuán et al ., ), which contributes to the increase in soil aggregate stability (Khotabaei et al ., ; Ibrahim et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…() showed that organic agricultural byproducts could be used as alternative low‐cost amendments to improve plant growth conditions in saline‐sodic soil without negative environmental effects. For example, straw and manures (Prapagar et al ., ; Adane et al ., ), composts (Abdel‐Fattah, ), municipal biosolids and vermicompost (Khotabaei et al ., ; Ibrahim et al ., ) and other organic wastes (Prapagar et al ., ; Diacono & Montemurro, ) have also been used in reclamation studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated the positive effect of vermicompost addition on soil bulk density (Azami et al, 2008;Gopinath et al, 2008;Ibrahim et al, 2015;Singh et al, 2013) and water holding capacity (Ganesh et al, 2011;Parthasarathi et al 2008).…”
Section: Physical Propertiesmentioning
confidence: 95%